EURASIP journal on information security - European Association for Speech, Signal and Image Processing ([Cairo, Egypt], 2007)
"The overall goal of the EURASIP Journal on Information Security, sponsored by the European Association for Signal Processing (EURASIP), is to bring together researchers and practitioners dealing with the general field of information security, with a particular emphasis on the use of signal processing tools to enable the security of digital contents. As such, it addresses any work whereby security primitives and multimedia signal processing are used together to ensure the secure access to the data. Enabling technologies include watermarking, data hiding, steganography and steganalysis, joint signal processing and encryption, perceptual hashing, identification, biometrics, fingerprinting, and digital forensics." -- Publisher's website.
Keywords: Computer security : Periodicals; Computer networks : Security measures : Periodicals; Computer networks : Security measures; Réseaux d'ordinateurs : Sécurité : Mesures; Sécurité informatique : Périodiques; Réseaux d'ordinateurs : Sécurité : Mesures : Périodiques; Computer networks : Security measures; Computer security; informatie; information; informatietechnologie; information technology; Information and Communication Technology (General); Informatie- en communicatietechnologie (algemeen)